2006
DOI: 10.1373/clinchem.2006.067439
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Concentration of Matrix Metalloproteinase-7 in Patients with Coronary Artery Disease

Abstract: Background: Plaque rupture is often associated with breakdown of the extracellular matrix in the shoulder region of a plaque. We tested whether plasma concentrations of various matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinase-1 (TIMP-1) could serve as markers for plaque instability as well as relationships between plasma MMPs and inflammatory markers. Methods: The study group included 65 men with angiographically verified CAD (45 with stable and 20 with unstable CAD) and 28 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 34 publications
(28 reference statements)
1
37
1
2
Order By: Relevance
“…25 In the present study, plasma MMP-7 levels demonstrated independent association with prevalent CVD among subjects with T2D. However, the association with atherosclerotic burden was not as pronounced as for MMP-12, and there was no association with the degree of arterial stiffness.…”
Section: Discussioncontrasting
confidence: 63%
“…25 In the present study, plasma MMP-7 levels demonstrated independent association with prevalent CVD among subjects with T2D. However, the association with atherosclerotic burden was not as pronounced as for MMP-12, and there was no association with the degree of arterial stiffness.…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, plasma concentrations of mmP-3 were 3-fold higher in the control group than in the group of ucad patients. in contrast, mmP-7 concentrations were increased by 50% in unstable cad patients compared to controls (4). Plasma mmP-9 concentration has been identified as a predictor of cardiovascular mortality in patients with cad (5).…”
Section: Introductionmentioning
confidence: 95%
“…in humans, plasma concentrations of different mmPs appear to vary depending on clinical status. for example, we have shown that plasma concentrations of mmP-2 were significantly decreased in patients with unstable coronary artery disease (ucad) compared with patients with stable cad and healthy controls (4). Similarly, plasma concentrations of mmP-3 were 3-fold higher in the control group than in the group of ucad patients.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP-7 is involved in N-cadherin cleavage and in vascular smooth muscle cell (VSMC) apoptosis, leading to fibrous cap thickness and to plaque instability . Nonetheless, MMP-7 is increased in patients with stable and unstable coronary artery disease (Nilsson et al, 2006). Furthermore, MMP-7 modulates the transcription of ADAM12, the main protease implicated in cardiac hypertension and hypertrophy ) (see Section 1.1.2): hence, knockdown of MMP-7 results in an attenuation of these pathological conditions.…”
Section: Matrilysinsmentioning
confidence: 99%